Speech Acts In The Students’ English Textbook For Junior High School - Suadnyani, Ni MAde Anik; Tantra, Dewa Komang; Dambayana S., Putu Eka (Universitas Pendidikan Ganesha, 2022)
The current research objective was to analyse the ninth grade students’ textbook in the Junior High School publishes by the Indonesia Ministry of National Education based on the 2013 Curriculum. The research problems were focused on the speech acts’ social functions, linguistic features, and language elements. The research was designed in a qualitative approach. Data were analysed descriptively by classifying the speech acts’ social functions, linguistic features, and language elements. The research findings were, firstly, the speech acts’ social functions were stating, describing, explaining, ordering, asking, advising, praying, requesting, complimenting, thanking, boasting, congratulating, apologizing, welcoming, condoling, refusing, offering, guaranteeing, and promising acts. Secondly, the speech acts’ linguistic features designed were imperative, interrogative, and declarative sentences. Thirdly, the speech acts’ language elements used were simple present tense, present continuous tense, present perfect tense, simple past tense, past continuous tense, past perfect tense, and simple future tense.